Inflammation and its genesis in cystic fibrosis. (3rd September 2015) - Nichols, David P.; Chmiel, James F.
Summary: The host inflammatory response in cystic fibrosis (CF) lung disease has long been recognized as a central pathological feature and an important therapeutic target. Indeed, many believe that bronchiectasis results largely from the oxidative and proteolytic damage comprised within an exuberant airway inflammatory response that is dominated by neutrophils. In this review, we address the longstanding argument of whether or not the inflammatory response is directly attributable to impairment of the cystic fibrosis transmembrane conductance regulator or only secondary to airway obstruction and chronic bacterial infection and challenge the importance of this distinction in the context of therapy. We also review the centrality of neutrophils in CF lung pathophysiology and highlight more recent data that suggest the importance of other cell types and signaling beyond NF‐κB activation. We discuss how protease and redox imbalance are critical factors in CF airway inflammation and end by reviewing some of the more promising therapeutic approaches now under development.Pediatr Pulmonol. 2015; 50:S39–S56. © 2015 Wiley Periodicals, Inc.